The Relationship between Attitudes towards Physical Activity and Self-Esteem of High School Students - KUCUKIBIS, H. Fatih; GUL, Mehmet (Asian Journal of Education and Training, 2019)
The purpose of this study was to examine the relationship between attitudes towards physical activity and self-esteem of high school students. Three different scales were used on 626 adolescents in total who lived in Sivas, found by random sampling method. The first scale is “the Personal Information Scale” consisting of 6 items to determine the demographical characteristics of the participants; the second scale is “the Cognitive Behavioral Physical Activity Questionnaire (CBPA)”, which was developed by Schembre et al. (2015) and was adapted to Turkish by Eskiler et al. (2016) to determine the participants’ attitudes towards physical activity; and the last scale is “the Self-Esteem Scale” by Rosenberg (1965) and adapted to Turkish by Çuhadaroğlu (1985) to determine the levels of self-esteem of the participants. The study data was analyzed by SPSS 25 package software. The obtained data were represented as values of frequency (f), percentage (%), average (x-), and standard deviation (±). Pearson Correlation analysis was applied in order to determine the effect of physical activity attitudes on self-esteem. The age average of the participants was determined to be 16,28 (±0,97). The gender distribution was 312 females and 314 males, and the number of those who were participating in licensed sports was 336, and that of those who were not was 290. It was determined that there was a positive correlation between the participants’ attitude towards physical activity and their self-esteem. In conclusion, a positive correlation was found between the attitude towards physical activity and self-esteem. In the study, it was suggested that the tendencies towards physical activity should be protected.